Longitudinal Changes in Work Ability, Well-Being, and Psychosocial Risk Factors Among Older Workers: The ProAgeing Study - Fattori, Alice; Barnini, Teresa; Comotti, Anna; Bufano, Pasquale; Laurino, Marco; Russo, Simone; Ferrari, Luca; Ciocan, Catalina; Bonzini, Matteo (La Medicina del Lavoro, 2025)
Background: As the workforce ages, older employees face increasing challenges in adapting to changing job demands, including technological advances and ongoing occupational risks such as shift work and physically demanding tasks. Work ability is a reliable indicator of older workers’ capacity to meet both physical and mental requirements of their jobs. The ProAgeing study, a multicenter investigation specifically focused on workers over 50 years old, examined long-term patterns in work ability, perceived health, and psychosocial risk factors, along with their interactions across this demographic. Methods: Participants completed self-reported questionnaires at baseline and after one year, including the Work Ability Index (WAI), technostress, sleep quality, perceived stress, health, and psychosocial risk factors. A first-difference linear regression model was used to assess predictors of changes in WAI. Subgroup analyses examined differences across occupational roles (bank employees, administrative employees, and manual workers). Results: Of the 470 workers enrolled, 356 (76%) completed the follow-up. A significant decline in average WAI score was observed over 12 months (-1.2 points, p